The Avant-Garde in Europe 1955-70 : The Collection of the Staedtisches Museum Moenchengladbach. - Scottish National Gallery of Modern Art, Edinburgh (Edinburgh : Scottish National Gallery of Modern Art)
Arman ; de Saint-Phalle, Niki ; Spoerri, Daniel ; Tinguely, Jean ; Group Zero ; Schoonhoven, Jan J. ; Piene, Otto ; Mack, Heinz ; Uecker, Guenther ; Fontana, Lucio ; Klein, Yves ; Manzoni, Piero ; Beuys, Joseph ; Broodthaers, Marcel ; etc.
The Avant-Garde in Europe 1955-70 : The Collection of the Staedtisches Museum Moenchengladbach, Scottish National Gallery of Modern Art, Edinburgh
boek